Productivity and Nitrogen Requirement of Maize (Zea mays L.) in Rabi as Influenced by Kharif Cropping Practices - Bharathi, S.; Veeraraghavaiah, R .; Rao, A. S.; Naidu, T. C. M.; Lakshmi, G. V. (International Journal of Bio-resource and Stress Management, 2015)
Devising fertilizer recommendations to a crop considering cropping sequence as a whole rather than an individual crop per se is economically sound and environmentally safe. Experiments were conducted on Vertisols of Regional Agriculture Research Station, Lam, Guntur, for two consecutive years, (2008-09 to 2009-10) to study N requirement of maize as influenced by preceding cropping practices. The crop residues/biomass turnout was registered in the order of sunnhemp>greengram with inorganic N>greengram with FYM>soybean with inorganic N>soybean with FYM during both the years of the study. The N turnout through crop residues/biomass across different kharif cropping practices, ranged from 17.7 kg ha-1 to 95 kg ha-1 and 17.3 kg ha-1 to 90.4 kg ha-1 during the first and the second year of the study, respectively. The growth parameters of rabi maize like plant height and dry matter accumulation were significantly increased by different preceding kharif cropping practices and N levels given to maize in sequence. During both the years of the study, significantly the highest kernel yield of maize was recorded with the application of 225 kg N ha-1 following sunnhemp in situ green manuring. Further, rabi maize following green gram and soybean in kharif with fertilizer N or FYM were significantly inferior to that following sunnhemp in situ greenmanuring but superior to that of following kharif fallow at all the levels of fertilizer N application. Fertilizer N replacement values estimated for different kharif cropping practices on succeeding maize ranged from 15 to 52 kg ha-1.